The Circle of Mountains A basque shepherding community - Ott, Sandra (Reno (Nevada), Las Vegas, London : University of Nevada Press, 1993)
The Background
The Setting and the People
The Seasonal Cycle
The Household
"First Neighbours"
The Church, the Priest and "Blessed Things"
Blessed Bread : A system of asymmetric exchange
"First Neighbour" Mortuary Obligations
The Olha : A pastoral institution
Rotation and Serial Replacement in the Olha : Past and present
Shepherding and Cheese-making
The Concept of Conception
TLS, 1/7/94, p. 10, W. A. Christian Jr.
1ère éd. 1981.
Bibliogr., index, glossaire, append.